Study of Sensitivity Index for Landslide Disaster in Gunungpati Sub-district, Semarang City - Mahendra Ken Pambayun; Muhammad Helmi; Fuad Muhammad (Universitas Diponegoro, 2024)
Sensitivity is one of the parameters of the vulnerability in a disaster. Gunungpati Sub-district is one of the sub-districts that had a high-intensity landslide in Semarang city. Assessment of the sensitivity index to disasters is necessary to reduce vulnerabilities and to become a consideration for policy-taking factors in the emergence of disasters. The sensitivity index uses the population density, building density, sex ratio, dependency ratio, poverty rate, and education level. The method used is a weighted scoring method for each sensitivity variable. The sensitivity index of the Gunungpati Sub-district on landslide ranges from 2.6 - 2.8. Sensitivity levels of the Gunungpati Sub-district are classified into three classes there are little sensitive, moderately sensitive, and sensitive classes. Five villages have high sensitivity values. Special attention from the government is needed to increase the capacity of the population in terms of social and economic aspects to reduce the high sensitivity value in the area. Mitigation that can be done by the government related to the sensitivity of this area can be through policies such as capital assistance and training for vulnerable groups, equalization of employment, making policies, and strict control of development permits in areas at risk of landslides.